A Dictionary of Atong A Tibeto-Burman Language of Northeast India and Bangladesh - Breugel, Seino van (Pacific linguistics ;, 2021)
Atong is a Tibeto-Burman language spoken in Northeast India and Bangladesh. In this dictionary, Seino van Breugel provides a rigorous, well-illustrated and well-referenced lexical description of the language, making this book of great interest and value to general linguists, typologists, as well as area specialists and cultural anthropologists. Comprising not only of an Atong-English, but also an English-Atong dictionary, as well as semantic lexica, this volume is one of the most thorough lexical descriptions of a Bodo-Garo language to date. The grammatical lexica allow the reader quick access to lists of members of the various Atong word classes, collocations and idiomatic expressions. The grammatical compendium makes this book self-contained, while its many references link it to the rest of the author's corpus on the Atong language. The appendix of photos not only provides visual illustrations to many of the Atong dictionary entries, but also offers the reader a glance at the physical environment in which the language is spoken.